Bridging the Horizon: A Collaborative and Cooperative Approach for Cross-cultural Learning on the Artistic and Architectural Heritages of Central and Northern Thailand. - Koompong Noobanjong; Chaturong Louhapensang (My University, 2015)
Following a successful 2013 cross-cultural educational experience, faculty members and students fromKing Mongkut's Institute of Technology, Ladkrabang (KMITL) and University of Colorado Denver (UCD) againorganized a series of workshops and field trips to investigate artistic and architectural heritages in central andnorthern Thailand in January 2015. The program concluded with a joint exhibition of student research projectsat KMITL. The research methodology for the 2015 KMITL-UCD workshops and excursions analyzes the programfor its roles in: 1) expanding student knowledge of the artistic and architecture heritages in central and northernThailand; and 2) bridging a horizon of understanding between two groups of students; one grounded in theirown cultural roots in Thailand and the other not. Informed by Spencer Kagan's notion of Cooperative andCollaborative (C&C) learning, this paper explores the value and significance of cross-cultural study andexchange and demonstrates the value of collaborative and cooperative learning in architectural education.
Keywords: Value (mathematics); Problem and Project Based Learning